Detection of charge dynamics of a tetraphenylporphyrin particle using GaAs-based nanowire enhanced by particle–metal tip capacitive coupling. (24th May 2017) - Okamoto, Shoma; Sato, Masaki; Sasaki, Kentaro; Kasai, Seiya
Abstract: We investigate a detection technique of charge dynamics of a molecular particle using a GaAs-based nanowire where the charge sensitivity is locally enhanced by particle–metal tip capacitive coupling. By equivalent circuit analysis, it was clarified that the nanowire channel potential becomes sensitive to the molecular particle on the nanowire when the particle is capacitively coupled with a metal tip. The concept was demonstrated using a GaAs-based nanowire with tetraphenylporphyrin (TPP) particles on its surface and a measurement system integrating an atomic force microscope (AFM) and a dynamic current measurement monitor/spectrum analyzer. When the metal tip was in contact with a TPP particle on the nanowire under an appropriate tip bias condition, random telegraph signal (RTS) noise was imposed on the nanowire current, suggesting the increase in sensitivity to the charge state of the particle by the metal tip contact. We discussed the origin of the RTS noise through analysis of the time constant of RTS noise, RTS amplitude, and noise spectrum.